Coincidence photoelectron measurements following 2p photoionization in Mg. (August 2015) - Sokell, Emma; Bolognesi, P; Safgren, Stephan; Long, Elaine; Avaldi, Lorenzo
Synopsis: Coincidence photoelectron spectroscopy has been used to test the two-step model of Auger decay following 2p photoionization in magnesium. Fitting of the data has yielded information on the dipole photoionization matrix elements as a function of photon energy.